2014
DOI: 10.1093/brain/awu306
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke fatigue: a deficit in corticomotor excitability?

Abstract: The pathophysiology of post-stroke fatigue is poorly understood although it is thought to be a consequence of central nervous system pathophysiology. In this study we investigate the relationship between corticomotor excitability and self-reported non-exercise related fatigue in chronic stroke population. Seventy first-time non-depressed stroke survivors (60.36 ± 12.4 years, 20 females, 56.81 ± 63 months post-stroke) with minimal motor and cognitive impairment were included in the cross-sectional observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
104
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 69 publications
10
104
0
1
Order By: Relevance
“…Those with slower movement speeds also reported heaviness of the affected limb,109 possibly a central sensory processing problem, which in turn may have led to choosing slower movement speeds. Those with slower movement speeds also exhibited low motor cortex excitability 106. It is unclear if these two findings have a direct relationship as it has previously been shown that motor cortex excitability does not encode movement speeds,110however, motor cortex excitability seems to be crucial in motor learning involving movement speeds 111.…”
Section: Mechanisms Of Psfmentioning
confidence: 97%
See 2 more Smart Citations
“…Those with slower movement speeds also reported heaviness of the affected limb,109 possibly a central sensory processing problem, which in turn may have led to choosing slower movement speeds. Those with slower movement speeds also exhibited low motor cortex excitability 106. It is unclear if these two findings have a direct relationship as it has previously been shown that motor cortex excitability does not encode movement speeds,110however, motor cortex excitability seems to be crucial in motor learning involving movement speeds 111.…”
Section: Mechanisms Of Psfmentioning
confidence: 97%
“…However, a closer look at these investigations show that tests used to identify motor deficits are normally questionnaire-based scores of activities of daily living such as Barthel index, Rankin scale and National Institutes of Health Stroke Scale 25 28 34 46 56 86 104 105. Some studies use laboratory-based tasks to measure motor function such as action research arm test, nine-hole peg test (NHPT), grip strength106 and scales such as Fugl-Meyer 107. These measures, although useful to identify gross motor limitations relevant to daily life, are not accurate measures of motor impairment.…”
Section: Mechanisms Of Psfmentioning
confidence: 99%
See 1 more Smart Citation
“…30,77 Physiologically, PSF appears be related to low excitability of corticospinal output and facilitatory synaptic inputs from cortical and subcortical sites. 85 Impaired motor control, as assessed by the Fugl-Meyer test, seems to be predictive of PSF. 41 …”
Section: Altered Cortical Excitability and Lesion Locationmentioning
confidence: 99%
“…Some researchers theorize that PSF may be associated with disturbances in cortical excitability. One study examining patients after stroke with minimal neurological deficits 85 found that PSF was explained, in part, by higher motor thresholds measured with transcranial magnetic stimulation. It was suggested that low excitability of both corticospinal output and its facilitatory synaptic inputs from cortical and subcortical sites may contribute to PSF.…”
Section: Altered Cortical Excitability and Lesion Locationmentioning
confidence: 99%